KONSEP KEMAKMURAN NEGARA DALAM HISTORIOGRAFI MELAYU ISLAM KURUN KE-13 HINGGA KE-19 (Concept of National Peace in Malay Muslim Historiography during 13th to 19th Century) - Denisova, Tatiana (Journal of Al-Tamaddun, 2012)
Literature of Malay Muslim historiography is one of the most essential historical resources in studying the history of Malay community, especially from the 13th to 19th century. Main texts such as Hikayat Raja Pasai (Chronicle King of Pasai), Sejarah Melayu (The Malay Annals), Hikayat Aceh, Peringatan Sejarah Negeri Johor, Hikayat Siak, Tuhfat al-Nafis represent numbers of streams in Islamic Malay historiography embedded in diversity of countries and time. These texts encompass info of the lifestyle of a society, aspect of economy and intellectual, politics, religion etc. Thus, analysis of these information assist us in understanding further the concept of the state existed during that period, including the concept of national peace or tranquility and secession and its main criteria. Furthermore, research of ancient Malay texts show that these concepts has strong relations to the characteristics of the ruler (e.g. just - unjust ruler) and the ways king rule their country as Islamic countries or states. Hence, these two concepts summarized in those texts are recognized as among of the concept of justice based on the principle of idealistic of Islamic government (Ideal Islamic state).